2022
DOI: 10.1097/gox.0000000000004047
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Subcostal Incision Scar with the Two-staged Abdominoplasty: An Innovative Approach

Abstract: Summary: Abdominoplasty is a commonly sought-after procedure due to its life-transforming results, but is limited, as in any other operation, by a number of contraindications. One of these contraindications is a subcostal scar, which may jeopardize blood supply to the upper flap of the abdominoplasty, resulting in skin necrosis. Herein, we challenge this dogma by introducing the two-staged abdominoplasty with the utilization of a delayed flap in a 48-year-old multiparous woman presenting with a Koch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…3 Nevertheless, strategies must be implemented to avoid complications and improve outcomes. 2,6 IRT has already been proven useful for plastic surgery, 7,9,10 with good acuity for evaluating tissue perfusion. 1,7 Several studies have reported its value in monitoring flap perfusion and preoperative perforator mapping.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Nevertheless, strategies must be implemented to avoid complications and improve outcomes. 2,6 IRT has already been proven useful for plastic surgery, 7,9,10 with good acuity for evaluating tissue perfusion. 1,7 Several studies have reported its value in monitoring flap perfusion and preoperative perforator mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons show reluctance to perform full abdominoplasty in patients with a previous subcostal incision because of the risk of vascular disruption. 2 , 3 , 6 This risk may be less, especially if previous surgery was performed in the remote past and other risk factors are absent. 3 Nevertheless, strategies must be implemented to avoid complications and improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations